(untitled) (Dermatology Reports, 2016)
Demodicosis is a common parasitic infection of the hair follicles and the pilosebaceous unit by the Demodex mites viz. Demodex folliculorum and Demodex brevis. Infection by this parasite is common among immunocompromised and elderly. We report a case of facial Demodicosis which presented like atypical rosacea with a gradually progressing swelling and redness on right side of face which was initially diagnosed as a case of Hansen’s disease. Skin biopsy revealed follicular dilatation with presence of Demodex mite along with intense perifollicular lymphomononuclear infiltrate. Patient was treated with oral tab Ivermectin 12 mg stat along with topical gel metronidazole twice daily to which he responded favourably.